The Onion (Allium cepa L.) R2R3-MYB Gene MYB1 Regulates Anthocyanin Biosynthesis - Schwinn, Kathy E.; Ngo, Hanh; Kenel, Fernand; Brummell, David A.; Albert, Nick W.; McCallum, John A.; Pither-Joyce, Meeghan; Crowhurst, Ross N.; Eady, Colin; Davies, Kevin M. (Frontiers in Plant Science, 2016)
Bulb colour is an important consumer trait for onion (Allium cepa L., Allioideae, Asparagales). The bulbs accumulate a range of flavonoid compounds, including anthocyanins (red), flavonols (pale yellow) and chalcones (bright yellow). Flavonoid regulation is poorly characterised in onion and in other plants belonging to the Asparagales, despite being a major plant order containing many important crop and ornamental species. R2R3-MYB transcription factors associated with the regulation of distinct branches of the flavonoid pathway were isolated from onion. These belonged to sub-groups (SGs) that commonly activate anthocyanin (SG6, MYB1) or flavonol (SG7, MYB29) production, or repress phenylpropanoid/flavonoid synthesis (SG4, MYB4, MYB5). MYB1 was demonstrated to be a positive regulator of anthocyanin biosynthesis by the induction of anthocyanin production in onion tissue when transiently overexpressd and by reduction of pigmentation when transiently repressed via RNAi. Furthermore, ectopic red pigmentation was observed in garlic (A. sativum L.) plants stably transformed with a construct for co-overexpression of MYB1 and a bHLH partner. MYB1 also was able to complement the acyanic petal phenotype of a defined R2R3-MYB anthocyanin mutant in Antirrhinum majus of the asterid clade of eudicots. The availability of sequence information for flavonoid-related MYBs from onion enabled phylogenetic groupings to be determined across monocotyledonous and dicotyledonous species, including the identification of characteristic amino acid motifs. This analysis suggests that divergent evolution of the R2R3-MYB family has occurred between Poaceae/Orchidaceae and Allioideae species. The DNA sequences identified will be valuable for future analysis of classical flavonoid genetic loci in Allium crops and will assist the breeding of these important crop species.